To Be Expressive or Not: The Role of Teachers’ Emotions in Students’ Learning - Wang, Yang (Frontiers in Psychology, 2022)
Understanding the role of teachers’ facial expressions in students’ learning is helpful to improve online teaching. Therefore, this study explored the effects of teacher’s facial expressions on students’ learning through analyzing three groups of video lectures. Participants were 78 students enrolled in three groups: one with an enhanced-expression teacher, one with a conventional-expression teacher, and one with the teacher’s audio only. ANOVA was used to explore whether video lectures instructed by the enhanced-expression teacher were better than those instructed by the conventional-expression teacher and the audio-only teacher for facilitating students’ learning, and what is the role of the teacher’s emotions in students’ perceived social presence, arousal level, cognitive load, and learning. The results showed that the video lecture by the enhanced-expression teacher was better than those with the conventional-expression teacher and with the audio-only for facilitating students’ social presence, arousal level, and long-term learning. Interestingly, it was found that the teacher’s emotions could relieve students’ cognitive load. These results explained the inconsistency of existing studies by exploring the mechanism of teachers’ emotions in students’ learning. It also provides teachers with practical guidance for video lecture design.